Oil spill remediation: Selectivity, sorption, and squeezing capacity of silicone composite foams filled with clinoptilolite. Issue 29 (26th May 2022) - Calabrese, Luigi; Piperopoulos, Elpida; Jovanovic, Vesna Stankov; Mitic, Violeta; Mitic, Milan; Milone, Candida; Proverbio, Edoardo
Abstract: Due to the enormous use of oil worldwide, accidental spills occur relatively often, threatening sea ecosystem. A remediation strategy, usually, includes materials of macroporous structure, flexibility, and low cost. Furthermore, they need to have oleophilic and hydrophobic characteristics. All these demands fulfill siloxane matrix foams. The addition of a natural zeolite, clinoptilolite, as filler, can improve their sorption characteristics and reusability. Silicone composite foams at different clinoptilolite content (35, 40, and 45 wt%) have been structurally characterized and evaluated by determining the sorption capacity in several liquids (naphtha, kerosene, pump oil, and water). The squeezing efficiency tests were performed to estimate the foams reusability. Compared with the unfilled one, the clinoptilolite filled foams shown lower sorption capacities with very high oil/water selectivity. The squeezing capacity of the foam with 40 wt% of clinoptilolite is equal to the unfilled foam for pump oil. In contrast, the squeezing capacity of 35 wt% clinoptilolite filled foam for naphtha oil is even higher. Compared to the foams, filled with other types of filler, the high effective oil selectivity of the foam with 35 wt% of clinoptilolite was proven, implying its superior suitability for light and heavy oils sorption. Abstract :